ANALYSIS OF STUDENTS' PERCEPTIONS ABOUT THE LANGUAGE OF INSTRUCTION IN HIGHER EDUCATION - Guneyli, Ahmet; Arsan, Nihan; Bashirova, Elnara (Hacettepe Univ, 2012)
Problem sentence of this research is what are the students' perceptions about the language of instruction in higher education? The research is qualitative and designed as a case study. Purposive and contrary/excessive case sampling is used and the study group is chosen from the students of Psychological Counseling and Guidance Department in Eastern Meditarranean University. Datas are obtained through Interview Form for Language of Instruction and focused group interview. Descriptive analysis is used. According to the results, most of the students are against teaching in foreign language and the most important problem was teaching based on memorizing. The problems can be removed by identifying and preventing all negative aspects that are influencing the quality of the instruction at the schools whose teaching is done in a foreign language.
Keywords: language of instruction; teaching in Turkish; teaching in foreign language; higher education